Polymer articles for ophthalmic products and methods of reducing propensity to polymer calcification

The method of creating fluorescent structures in polymers through UV irradiation and heat treatment effectively reduces calcification in IOLs, enhancing biocompatibility and optical clarity without additional chemicals, addressing the challenge of hydrophilic IOL clouding.

CN119213335APending Publication Date: 2024-12-27ACTIOL GMBH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380026050.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-08
Filing Date
2023-03-07
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Hydrophilic intraocular lenses (IOLs) are prone to calcification, leading to clouding and vision impairment, with existing solutions being complex, costly, or ineffective, and there is a lack of reliable methods to reduce this risk without adding chemicals or using expensive equipment.

Method used

A method involving the production of fluorescent structures in or on the polymer articles, such as IOLs, through UV irradiation and/or heating above the glass transition temperature, which reduces calcification tendency without adding chemicals, using physical means like UV radiation and heat treatment to create cyclic structures within the polymer chains.

Benefits of technology

Significantly reduces the calcification tendency of hydrophilic and hydrophobic polymers by up to 100%, ensuring biocompatibility and optical clarity, while avoiding the need for additional chemicals and costly processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213335A_ABST
    Figure CN119213335A_ABST
Patent Text Reader

Abstract

A method for reducing the propensity to calcification of a polymeric article is disclosed. The method comprises irradiating and / or heating a polymer, in particular a hydrophilic polymer for an intraocular lens, by UV light to achieve blue fluorescence of the polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the calcification tendency of a polymer product, in particular to a hydrophilic polymer product for intraocular lenses, and provides a method for reducing the calcification tendency thereof. Background Art

[0002] A common problem with polymers used in optical lenses for human use is their tendency to cloud over time. This occurs in particular with intraocular lenses (IOLs). The cause of the clouding is the formation of calcium deposits up to about 40 μm deep (calcium phosphate in different crystalline forms) on the surface and in the superficial layers. This phenomenon is known in the art by the term "calcification". Hydrophilic polymers are more susceptible to calcification than hydrophobic polymers.

[0003] IOLs show calcification in vivo to the extent that the intraocular lens of the eye becomes cloudy and requires replacement of the implant to restore vision. P. Kanclerz et al., Curr. Opin. Ophthalmol. (2021), 32, 31-44 and A. Grzybowski et al., Ann. Transl. Med. (2020), 8, 1547-1547 have found that the incidence of this phenomenon is <1% of all implanted hydrophilic IOLs, regardless of manufacturer, but some batches from certain manufacturers show a significantly higher risk of (nano) calcification.

[0004] Although the probability of (nano)calcification impairing vision is clearly in the one in a thousand range, hydrophilic intraocular lenses are used less and less. However, hydrophilic polymers containing from 15 wt.-% to almost 50 wt.-% water more strongly resemble the natural lens of the eye and are more biocompatible than hydrophobic polymers. In addition to reduced biocompatibility, hydrophobic polymers often tend to reflect light, which causes a severe reduction in visual acuity.

[0005] The research conducted so far in this area of ​​technology has provided the following insights: Calcification propensity depends primarily on two factors, the patient and the IOL material. Regarding the patient, there is generally a consensus that diabetes is an important factor, as it increases vascular porosity, leading to Ca 2+ Furthermore, there may be a calcification effect of the air cushion used in corneal transplantation on the implanted IOL.

[0006] In the prior art, different solutions have been proposed to eliminate or at least further minimize calcifications, since in order to restore vision, the patient would necessarily have to undergo other uncomfortable eye surgeries that are expensive and cannot be repeated indefinitely, due to the increasing difficulty of positioning and fixing the lens.

[0007] In the case of frequently occurring calcifications in batches, A. Grzybowski et al. report that by adapting the packaging process, in particular by eliminating silicone-containing materials, it has been possible to reduce this risk to normal levels.

[0008] In addition, it is believed that the use of high-purity starting materials in the polymerization can generally achieve a reduced risk of calcification formation. Another solution to combat calcification is the hydrophobic surface modification of the lens. However, JF Costa et al., Eur. J. Ophthalmol. (2020), 30, 307-314 and SP Gartaganis et al., Am. J. Ophthalmol. (2016), 168, 68-77 reported that in this case there is even an increased incidence of calcification.

[0009] For example, US2017 / 0172728A1 discloses an IOL prepared by forming a hydrophobic poly(p-xylene) skin by chemical vapor deposition (CVD) encapsulating a liquid hydrophilic core. However, the method is very complex and requires expensive equipment. In addition, the optical quality of the lens is difficult to determine, which is attributed to the encapsulation process of the liquid core, in which a drop of liquid is placed on a first CVD-produced poly(p-xylene) skin and a second poly(p-xylene) skin is deposited directly on the liquid. The poly(p-xylene) is applied in a vacuum and creates a hydrophobic surface, but before implantation, the hydrophilic material needs to absorb a considerable amount of water to achieve the most common 20-30 wt.-% water.

[0010] Although their high water content bodes well for better biocompatibility, persistent calcification issues have resulted in hydrophilic IOLs being increasingly replaced by hydrophobic IOLs.

[0011] For the production of hydrophilic IOLs, there is an urgent need to obtain materials and methods that can significantly further reduce the risk of postoperative (nano)calcification.

[0012] Currently, there are no available methods by which the occurrence of calcification in intraocular lenses in general and hydrophilic IOLs in particular can be reliably reduced. There is not even an established test to quantify the risk of (nano)calcification of IOLs on a batch level.

[0013] The object of the present invention is therefore to provide a method for reducing the calcification tendency of polymeric articles. In particular, the method should not require the addition of further chemicals or expensive equipment to the polymer. Furthermore, the method is to act on polymeric articles and should be able to process a large number of articles, such as IOLs, in a short time. Finally, articles, in particular ophthalmic medical aids, are to be provided with a reduced calcification tendency. Summary of the invention

[0014] These objects are achieved by means of the methods, products and uses of the independent claims. Preferred embodiments are the subject matter of the dependent claims.

[0015] The features of the polymers and articles achieved by the process of the present invention also apply to the claimed articles, since the polymer of the article is the same.

[0016] In the context of this application, polymer articles include "bulk volume" and "skin layer". These terms refer to the polymer volume of the article between its outer surface, where the outer surface refers to the interface between the polymer and the surrounding atmosphere and does not refer to the outer surface of the hollow body. In the cross section of the article or the wall of the article, the "skin layer" extends from the surface into the article 300 μm and surrounds the bulk volume.

[0017] A method for reducing the calcification tendency of an article, optionally formed as an optical lens, an intraocular lens, or a button or preform of an optical lens or intraocular lens, comprises producing one or more fluorescent structures in or on the article, wherein the article comprises one or more polymers, wherein the one or more polymers comprise an acrylic structural motive. The polymer is particularly a biocompatible polymer.

[0018] The term "calcification tendency" refers to the degree of calcification determined by a 90-day incubation test at 35°C in incubation solution L3 (see below) and is defined as the ratio between the areas of calcium deposits on or in the article within the measured area. Both terms are used interchangeably within the present application.

[0019] As used within the scope of this application, acrylic structural motifs refer to repeating units of polymers which are based on monomers of substituted or unsubstituted (meth)acrylic acid or its esters and amides.

[0020] Producing the one or more fluorescent structures may include partially or fully irradiating the article with UV radiation, preferably having a wavelength of 220 nm to 380 nm, and / or heating the article above the glass transition temperature, Tg, of the polymer.

[0021] The inventors have surprisingly found that it is possible to treat polymers for IOLs using only physical means in such a way that a polymer which is non-fluorescent per se exhibits clear fluorescence. And it has been demonstrated in in vitro stress tests that the tendency to calcification is significantly reduced after the method has been carried out. The method of the invention is particularly effective for hydrophilic polymers which are generally used for ophthalmic medical aids, and also for corresponding hydrophobic polymers. Cyclic hydrocarbon structures produced by heat treatment or irradiation within the polymer chains (intramolecular) or between them (intermolecular) may be the cause of the fluorescence. If heat treatment is carried out, the polymer can be used as a crude product, i.e. a preform (already in the shape of a lens, but not yet formed into the desired optical shape) or a so-called "button" or "round blank" (core-like shape), or, if irradiation is carried out, as a finished IOL.

[0022] The reason for this difference is that the heat treatment acts on the bulk material, while the irradiation treatment acts only on the surface layers. Medical regulations for IOLs require that UV light irradiation treatments be limited to the surface layers by adding UV absorbers to the polymer. The term "UV absorber" refers to chemicals or compounds that absorb UV radiation and thus reduce the transmission of UV radiation in the UV-A, UV-B and / or UV-C range through the IOL. Examples of UV absorbing compounds used are 4-(2-acryloyloxyethoxy)-2-hydroxybenzophenone (AEHB) and 2-(4-benzoyl-3-hydroxyphenoxy)ethyl acrylate. Thus, depending on the irradiation time, the fluorescence effect occurs up to a depth of 50-200 μm.

[0023] The present invention describes for the first time a method by which the occurrence of calcification can be specifically reduced in vitro.

[0024] Two examples of reactions that produce cyclic structures in acrylate polymers are shown in the reaction schemes below.

[0025]

[0026] These reactions do not require oxygen. They are photoinduced free radical reactions that produce fluorescent cyclic products. A particularly common structure that can be found in fluorescent polymers is a lactone structure containing a 1-oxacycloalkane-2-one structure (i.e., a cyclic carboxylate ester is present) or an analog with unsaturated or heteroatoms, especially nitrogen, replacing one or more ring carbon atoms. Examples of such lactone structures are also shown in Schemes 1 and 2 above.

[0027] The method for reducing the calcification tendency of a polymer article for the production of a polymer optical lens according to the present invention comprises generating one or more fluorescent structures. Generating one or more fluorescent structures may comprise generating fluorescent structures in a polymer, in particular by generating substituents and / or structural units of the polymer chain through intramolecular and / or intermolecular condensation. This may ultimately be followed by other reactions. In particular, this may be performed without adding chemicals.

[0028] Fluorescent structures can be generated inside the polymer as independent substances or structures. In particular, fluorescent structures may not be extractable from the polymer product. In the context of the present invention, "non-extractable" structures or substances refer to structures or substances that cannot be extracted by an extraction method such as that used to determine the extract content according to Annex A of DIN EN ISO 11979-5:2010-11 using methanol as a solvent. That is, the results of the extraction test remain the same before and after the treatment according to the present invention. Since the extract of the polymer product does not contain any fluorescent compounds, the inventors believe that at least most of the fluorescence is generated by the structures inside the polymer chain.

[0029] A significant advantage of the method of the present invention is that it reduces the calcification tendency without having to add chemicals to the polymer in order to reduce the calcification tendency. Such chemicals may subsequently migrate from the lens while the patient is wearing the lens and cause eye irritation.

[0030] Another significant advantage is that since no additional chemicals are added, the polymer remains essentially the same, eliminating the need to meet a new lens approval process, which would otherwise be associated with significant expense.

[0031] Polymer preparation calcification can be quantified by following the incubation test procedure as an in vitro calcification assay.

[0032] The article to be tested (e.g. blank or IOL) is placed in a test cuvette containing an incubation solution selected from L1-L4 (see Table 1) and incubated at 35°C in the dark. Optionally, incubation solution L4 is used, since it has the highest concentration and requires the shortest incubation time to show the result. Other solutions may be selected if slight differences between similarly executed samples should be investigated.

[0033] Table 1

[0034]

[0035] The sample is measured at regular intervals with a metrology device comprising a white light source behind the sample and an electronic camera located in front of the sample. The camera records a focal stack of images which is processed into an image with a high depth of field.

[0036] This image is further processed and decomposed into dark areas (identifiable by white reflections) and transparent areas. All areas with less than 95% transparency are considered calcifications. When measuring, no distinction is made between superficial calcifications and those inside the material.

[0037] As the degree of calcification, the ratio of the calcified area divided by the total measured area is calculated. This ratio can also be described in other terms as the percentage of the sample area that is turbid with calcium deposits. Thus, the reduction in the degree of calcification can be calculated by dividing the degree of calcification of the treated sample by the degree of calcification of the untreated sample and subtracting 1 from the result.

[0038] In an embodiment, the calcification tendency of the polymer is reduced by 50% as compared to before treatment. To determine the reduction in calcification tendency, the calcification degree of the polymer can be determined in the incubation test procedure mentioned above using solution L3 at 35°C and an incubation time of 90 days. Preferably, the calcification tendency is reduced by at least 55%, or at least 60%, or at least 65%, or at least 70%, or at least 75%, or at least 80%, or at least 85%, or at least 90%, or at least 95%, or at least 99%, or at least 99.5%. The calcification tendency can also be reduced by 100%. The calcification tendency of the polymer can be reduced by at most 55%, or at most 60%, or at most 65%, or at most 70%, or at most 75%, or at most 80%, or at most 85%, or at most 90%, or at most 95%, or at most 99%, or at most 99.5%. The calcification tendency of the polymer may be reduced by 50%-100% or 50%-99.5% or 50%-99% or 50%-95% or 50%-90% or 50%-85% or 50%-80% or 50%-75% or 50%-70% or 50%-65% or 50%-60% or 50%-55%. The calcification tendency of the polymer may be reduced by 55%-100% or 55%-99.5% or 55%-99% or 55%-95% or 55%-90% or 55%-85% or 55%-80% or 55%-75% or 55%-70% or 55%-65% or 55%-60%. The calcification tendency of the polymer may be reduced by 60%-100% or 60%-99.5% or 60%-99% or 60%-95% or 60%-90% or 60%-85% or 60%-80% or 60%-75% or 60%-70% or 60%-65%. The calcification tendency of the polymer may be reduced by 65%-100% or 65%-99.5% or 65%-99% or 65%-95% or 65%-90% or 65%-85% or 65%-80% or 65%-75% or 65%-70%. The calcification tendency of the polymer may be reduced by 70%-100% or 70%-99.5% or 70%-99% or 70%-95% or 70%-90% or 70%-85% or 70%-80% or 70%-75%. The calcification tendency of the polymer may be reduced by 75%-100% or 75%-99.5% or 75%-99% or 75%-95% or 75%-90% or 75%-85% or 75%-80%. The calcification tendency of the polymer may be reduced by 80%-100% or 80%-99.5% or 80%-99% or 80%-95% or 80%-90% or 80%-85%. The calcification tendency of the polymer may be reduced by 85%-100% or 85%-99.5% or 85%-99% or 85%-95% or 85%-90%. The calcification tendency of the polymer may be reduced by 90%-100% or 90%-99.5% or 90%-99% or 90%-95%.The calcification tendency of the polymer can be reduced by 95%-100% or 95%-99.5% or 95%-99%. The calcification tendency of the polymer can be reduced by 99%-100% or 99%-99.5%. The calcification tendency of the polymer can be reduced by 99.5%-100%. Particularly preferred reductions in calcification tendency ranges are, for example, 50%-100%, 60%-95% or 70%-90%.

[0039] The polymer articles treated according to the present invention preferably have a calcification tendency of less than 10% or less than 9% or less than 8% or less than 7% or less than 6% or less than 5% or less than 4% or less than 3% or less than 2% or less than 1% (as measured in the incubation test procedure described above using solution L3 at 35°C for 90 days). It is worth noting that the calcification test described herein is much harsher than physiological conditions, i.e. if the calcification is low in this test, it can be assumed that calcification will not occur under physiological conditions.

[0040] The polymer of the present invention will increase the fluorescence intensity with the treatment time until the maximum value by UV irradiation. The maximum value is specific to the product. It is determined by continuing UV irradiation until no further increase can be obtained. "No further increase" means that the difference between two fluorescence intensity values ​​(in arbitrary units (au)) is less than 3% using a fluorescence spectrometer using an excitation wavelength of 365nm. Once this maximum value is reached, further treatment will not further enhance the fluorescence intensity. In an embodiment, one or more fluorescent structures are produced so that the fluorescence intensity of the product is at least 80% of the maximum intensity that can be achieved in the product by UV irradiation. It is preferably possible to implement a treatment sufficient to achieve at least 85% or at least 86% or at least 87% or at least 88% or at least 89% or at least 90% or at least 91% or at least 92% or at least 93% or at least 94% or at least 95% of the maximum intensity.

[0041] In case of thermal treatment, ie heating above Tg, the process can be continued until fluorescence values ​​comparable to those obtained by UV irradiation are obtained.

[0042] In a preferred embodiment of the method and the article, the polymer is a hydrophilic polymer and / or has a water absorption of 5 wt.-% to 50 wt.-% at a temperature of 25°C (determined according to DIN EN ISO 18369-4:2018-04 Section 4.6). Preferably, the water absorption is 20 wt.-% to 40 wt.-% at a temperature of 25°C. The water absorption may be at least 5 wt.-% or at least 10 wt.-% or at least 15 wt.-% or at least 20 wt.-% at a temperature of 25°C. The water absorption may be at most 50 wt.-% or at most 45 wt.-% or at most 40 wt.-% or at most 35 wt.-% at a temperature of 25°C.

[0043] On the one hand, hydrophilic polymers, especially with such water absorption, are more biocompatible than hydrophobic polymers and on the other hand, they are the polymers most responsive to the method, i.e. they readily form fluorescent structures and the reduction of calcification is more pronounced.

[0044] The polymers of the methods and articles of the present invention are homopolymers or copolymers of (meth)acrylates, acrylamides and / or alkylene glycols.

[0045] Most preferably, the polymer of the present method and article is a homopolymer or copolymer of monomers selected from the group consisting of methyl methacrylate (MMA), 2-hydroxyethyl methacrylate (HEMA), 2-hydroxyethyl acrylate (HEA), butyl acrylate (BA), lauryl acrylate (LA), ethoxyethyl methacrylate (EOEMA), methacrylic acid (MAA), acrylamide (AA), ethylene glycol dimethacrylate (EGDMA), diethylene glycol dimethacrylate (DEGMA), butanediol diacrylate (BDDA), N,N'-methylenebis(acrylamide) (MBA), ethylene glycol, propylene glycol, poly(ethylene glycol) phenyl ether acrylate (PEGPEA) and 2-phenylphenoxyethyl acrylate (OPPEA). The copolymers may contain only the aforementioned monomers or may also contain other monomers wherein the aforementioned monomers form more than 50 mol-% of the copolymer. These specific hydrophilic and hydrophobic homopolymers and copolymers are most effectively treated with the present method. The method of the invention achieves a reduction in the risk of calcification of at least 50% for all hydrophilic polymers based on MMA or its derivatives (eg HEMA), for example.

[0046] When used in the method of the invention, the polymer article may have the shape of an intraocular lens, an intraocular lens "button" or a preform. The fluorescent structure may be conveniently produced on the finished product, i.e. as an additional final step of the normal production process known in the prior art. Thus, the normal working flow will not need to be changed and only non-defective lenses will be processed. However, it is also possible to process the preform of the IOL before the lens is formed.

[0047] Most preferably, the step of producing the fluorescent structure comprises irradiating the polymer with UV radiation and / or heating the polymer above its glass transition temperature Tg. The glass transition temperature Tg can be determined according to DIN 51007:2019-04. Preferably, the UV radiation has a wavelength of 250nm-380nm, more preferably 265nm-350nm or 265nm-315nm. Preferably, the heat treatment is moderately carried out above Tg, especially in the range of (Tg+1°C)-(Tg+130°C) or more preferably in the range of (Tg+1°C)-(Tg+100°C) or (Tg+1°C)-(Tg+70°C) or (Tg+5°C)-(Tg+50°C).

[0048] Fluorescent structures can be produced by irradiation or heating above Tg, either alone or in combination. When irradiating a polymer article, fluorescence is produced only in the surface layer of the polymer, extending 300 μm into the body of the article. Only after the irradiation time is increased does the fluorescence effect extend into the body up to about 200 μm. For the most commonly used irradiation times, the effect is limited to a depth of about 70 μm-100 μm, which is still sufficient to achieve the desired reduction in calcification. When heating the polymer, fluorescent structures are produced uniformly throughout the body. Both effects can be used to adjust the desired effect. The combination can help reduce processing time. The combination can also be used to customize surface effects related to volume effects.

[0049] In order to be able to fold and unfold the lens during the process of insertion into the patient's eye, the polymer should have a certain hardness range. If the material is too hard, the lens will be difficult to fold, and insufficient rigidity will prevent the lens from properly unfolding in the eye. If the material exceeds the required range, the lens may be damaged or even broken during insertion. Generally, the VLRH (very low rubber hardness) hardness measured according to DIN ISO 27588:2014-12 for photochemically treated hydrophilic polymers is very small and below the analytical resolution. For heat-treated polymers, the VLRH hardness increases by about 1-2 units of VLRH, for example, from 88.5VLRH-89VLRH to 90VLRH-90.5VLRH for the common hydrophilic polymers tested. In one embodiment, the polymer has a hardness of 80VLRH-100VLRH, preferably 85VLRH-95VLRH.

[0050] The increase in hardness is small and does not affect the folding of lenses made of the treated material.

[0051] Since the creation of fluorescent structures also affects other properties of the polymer, such as hydrophobicity and hardness, it is important that the choice between irradiation treatment and thermal treatment is also based on the desired changes in these properties in the bulk or just on the polymer surface.

[0052] For treatment, the polymer lens or preform is mounted in a holder and irradiated with a UV lamp (e.g. a mercury lamp or UV-LED), and / or heated above its glass transition temperature for a sufficient time until blue fluorescence develops. This can be visually controlled or automated with the aid of a sensor. The lens or preform is then turned and irradiated a second time from the back side. Alternatively, they can be irradiated from both sides simultaneously. In the case of thermal treatment, this step is not required due to the volume effect.

[0053] In some embodiments, the irradiation and / or heating is carried out at a reduced pressure, i.e., at a pressure below ambient pressure, preferably at an absolute pressure of ≤900 hectopascals (hPa). The absolute pressure may be, for example, ≤900 hPa or ≤800 hPa or ≤700 hPa or ≤600 hPa or ≤500 hPa or ≤400 hPa or ≤300 hPa or ≤200 hPa or ≤100 hPa or ≤50 hPa or ≤10 hPa. The absolute pressure may be, for example, ≥800 hPa or ≥700 hPa or ≥600 hPa or ≥500 hPa or ≥400 hPa or ≥300 hPa or ≥200 hPa or ≥100 hPa or ≥50 hPa or ≥10 hPa or ≥1 hPa or ≥0.1 hPa or ≥0.01 hPa or ≥0.001 hPa. The absolute pressure may be, for example, 0.001 hPa-900 hPa or 0.001 hPa-800 hPa or 0.001 hPa-700 hPa or 0.001 hPa-600 hPa or 0.001 hPa-500 hPa or 0.001 hPa-400 hPa or 0.001 hPa-300 hPa or 0.001 hPa-200 hPa or 0.001 hPa-100 hPa or 0.001 hPa-50 hPa or 0.001 hPa-10 hPa or 0.001 hPa-1 hPa or 0.001 hPa-0.1 hPa or 0.001 hPa-0.01 hPa. The absolute pressure may for example be 0.01 hPa-900 hPa or 0.01 hPa-800 hPa or 0.01 hPa-700 hPa or 0.01 hPa-600 hPa or 0.01 hPa-500 hPa or 0.01 hPa-400 hPa or 0.01 hPa-300 hPa or 0.01 hPa-200 hPa or 0.01 hPa-100 hPa or 0.01 hPa-50 hPa or 0.01 hPa-10 hPa or 0.01 hPa-1 hPa or 0.01 hPa-0.1 hPa. The absolute pressure may for example be 0.1 hPa-900 hPa or 0.1 hPa-800 hPa or 0.1 hPa-700 hPa or 0.1 hPa-600 hPa or 0.1 hPa-500 hPa or 0.1 hPa-400 hPa or 0.1 hPa-300 hPa or 0.1 hPa-200 hPa or 0.1 hPa-100 hPa or 0.1 hPa-50 hPa or 0.1 hPa-10 hPa or 0.1 hPa-1 hPa.The absolute pressure may be, for example, 1 hPa-900 hPa or 1 hPa-800 hPa or 1 hPa-700 hPa or 1 hPa-600 hPa or 1 hPa-500 hPa or 1 hPa-400 hPa or 1 hPa-300 hPa or 1 hPa-200 hPa or 1 hPa-100 hPa or 1 hPa-50 hPa or 1 hPa-10 hPa. The absolute pressure may be, for example, 10 hPa-900 hPa or 10 hPa-800 hPa or 10 hPa-700 hPa or 10 hPa-600 hPa or 10 hPa-500 hPa or 10 hPa-400 hPa or 10 hPa-300 hPa or 10 hPa-200 hPa or 10 hPa-100 hPa or 10 hPa-50 hPa. The absolute pressure may be, for example, 50 hPa-900 hPa or 50 hPa-800 hPa or 50 hPa-700 hPa or 50 hPa-600 hPa or 50 hPa-500 hPa or 50 hPa-400 hPa or 50 hPa-300 hPa or 50 hPa-200 hPa or 50 hPa-100 hPa. The absolute pressure may be, for example, 100 hPa-900 hPa or 100 hPa-800 hPa or 100 hPa-700 hPa or 100 hPa-600 hPa or 100 hPa-500 hPa or 100 hPa-400 hPa or 100 hPa-300 hPa or 100 hPa-200 hPa. The absolute pressure may be, for example, 200 hPa-900 hPa or 200 hPa-800 hPa or 200 hPa-700 hPa or 200 hPa-600 hPa or 200 hPa-500 hPa or 200 hPa-400 hPa or 200 hPa-300 hPa. The absolute pressure may be, for example, 300 hPa-900 hPa or 300 hPa-800 hPa or 300 hPa-700 hPa or 300 hPa-600 hPa or 300 hPa-500 hPa or 300 hPa-400 hPa. The absolute pressure may be, for example, 400 hPa-900 hPa or 400 hPa-800 hPa or 400 hPa-700 hPa or 400 hPa-600 hPa or 400 hPa-500 hPa. The absolute pressure may be, for example, 500 hPa-900 hPa or 500 hPa-800 hPa or 500 hPa-700 hPa or 500 hPa-600 hPa. The absolute pressure may be, for example, 600 hPa-900 hPa or 600 hPa-800 hPa or 600 hPa-700 hPa. The absolute pressure may be, for example, 700 hPa-900 hPa or 700 hPa-800 hPa. The absolute pressure may be, for example, 800 hPa-900 hPa.Particularly preferred absolute pressure ranges are, for example, 0.001 hPa to 900 hPa, 0.001 hPa to 200 hPa, 0.001 hPa to 100 hPa or 0.01 hPa to 10 hPa. Reduced pressure is advantageous for the removal of low molecular weight products that may be produced during the process.

[0054] Furthermore, it is advantageous if the content of residual monomers in the polymer is low or reduced before the step of producing the fluorescent structure. Preferably, this content is reduced to a concentration of <1 wt.-%, more preferably <0.9 wt.-% or <0.8 wt.-% or <0.7 wt.-% or <0.6 wt.-% or <0.5 wt.-% or <0.4 wt.-% or <0.3 wt.-% or <0.2 wt.-% or <0.1 wt.-% relative to the total amount of polymer. It may be reduced to a concentration of >0.9 wt.-% or >0.8 wt.-% or >0.7 wt.-% or >0.6 wt.-% or >0.5 wt.-% or >0.4 wt.-% or >0.3 wt.-% or >0.2 wt.-% or >0.1 wt.-% or >0.01 wt.-% or >0.001 wt.-% or >0.0001 wt.-%. It can be reduced to a concentration of 0.0001wt.-% -<1wt.-% or 0.0001wt.-% -<0.9wt.-% or 0.0001wt.-% -<0.8wt.-% or 0.0001wt.-% -<0.7wt.-% or 0.0001wt.-% -<0.6wt.-% or 0.0001wt.-% -<0.5wt.-% or 0.0001wt.-% -<0.4wt.-% or 0.0001wt.-% -<0.3wt.-% or 0.0001wt.-% -<0.2wt.-% or 0.0001wt.-% -<0.1wt.-% or 0.0001wt.-% -<0.01wt.-% or 0.0001wt.-% -<0.001wt.-%. It can be reduced to a concentration of 0.001wt.-% -<1wt.-% or 0.001wt.-% -<0.9wt.-% or 0.001wt.-% -<0.8wt.-% or 0.001wt.-% -<0.7wt.-% or 0.001wt.-% -<0.6wt.-% or 0.001wt.-% -<0.5wt.-% or 0.001wt.-% -<0.4wt.-% or 0.001wt.-% -<0.3wt.-% or 0.001wt.-% -<0.2wt.-% or 0.001wt.-% -<0.1wt.-% or 0.001wt.-% -<0.01wt.-%.It can be reduced to a concentration of 0.01wt.-% -<1wt.-% or 0.01wt.-% -<0.9wt.-% or 0.01wt.-% -<0.8wt.-% or 0.01wt.-% -<0.7wt.-% or 0.01wt.-% -<0.6wt.-% or 0.01wt.-% -<0.5wt.-% or 0.01wt.-% -<0.4wt.-% or 0.01wt.-% -<0.3wt.-% or 0.01wt.-% -<0.2wt.-% or 0.01wt.-% -<0.1wt.-%. It can be reduced to a concentration of 0.1wt.-% -<1wt.-% or 0.1wt.-% -<0.9wt.-% or 0.1wt.-% -<0.8wt.-% or 0.1wt.-% -<0.7wt.-% or 0.1wt.-% -<0.6wt.-% or 0.1wt.-% -<0.5wt.-% or 0.1wt.-% -<0.4wt.-% or 0.1wt.-% -<0.3wt.-% or 0.1wt.-% -<0.2wt.-%. It can be reduced to a concentration of 0.2wt.-% - <1wt.-% or 0.2wt.-% - <0.9wt.-% or 0.2wt.-% - <0.8wt.-% or 0.2wt.-% - <0.7wt.-% or 0.2wt.-% - <0.6wt.-% or 0.2wt.-% - <0.5wt.-% or 0.2wt.-% - <0.4wt.-% or 0.2wt.-% - <0.3wt.-%. It can be reduced to a concentration of 0.3wt.-%-<1wt.-% or 0.3wt.-%-<0.9wt.-% or 0.3wt.-%-<0.8wt.-% or 0.3wt.-%-<0.7wt.-% or 0.3wt.-%-<0.6wt.-% or 0.3wt.-%-<0.5wt.-% or 0.3wt.-%-<0.4wt.-%. It can be reduced to a concentration of 0.4wt.-%-<1wt.-% or 0.4wt.-%-<0.9wt.-% or 0.4wt.-%-<0.8wt.-% or 0.4wt.-%-<0.7wt.-% or 0.4wt.-%-<0.6wt.-% or 0.4wt.-%-<0.5wt.-%. It can be reduced to a concentration of 0.5wt.-%-<1wt.-% or 0.5wt.-%-<0.9wt.-% or 0.5wt.-%-<0.8wt.-% or 0.5wt.-%-<0.7wt.-% or 0.5wt.-%-<0.6wt.-%. It can be reduced to a concentration of 0.6wt.-%-<1wt.-% or 0.6wt.-%-<0.9wt.-% or 0.6wt.-%-<0.8wt.-% or 0.6wt.-%-<0.7wt.-%.It can be reduced to a concentration of 0.7wt.-%-<1wt.-% or 0.7wt.-%-<0.9wt.-% or 0.7wt.-%-<0.8wt.-%. It can be reduced to a concentration of 0.8wt.-%-<1wt.-% or 0.8wt.-%-<0.9wt.-%. It can be reduced to a concentration of 0.9wt.-%-<1wt.-%. A particularly preferred concentration range is, for example, 0.0001wt.-%-<0.9wt.-%, 0.001wt.-%-<0.7wt.-% or 0.001wt.-%-<0.5wt.-%. The content of residual monomers in the polymer is particularly preferably reduced as much as possible. The optional elimination of residual monomers promotes the formation of fluorescent structures because there is no competitive reaction between the monomers and the generated structures.

[0055] In a preferred embodiment, the method comprises reducing the content of residual monomers in the polymer. Reducing the content of residual monomers can preferably be achieved by extraction or applying a reduced pressure, i.e. a pressure below ambient pressure, preferably an absolute pressure of ≤900 hPa. The absolute pressure can be, for example, ≤900 hPa or ≤800 hPa or ≤700 hPa or ≤600 hPa or ≤500 hPa or ≤400 hPa or ≤300 hPa or ≤200 hPa or ≤100 hPa or ≤50 hPa or ≤10 hPa or ≤1 hPa. The absolute pressure can be, for example, ≥800 hPa or ≥700 hPa or ≥600 hPa or ≥500 hPa or ≥400 hPa or ≥300 hPa or ≥200 hPa or ≥100 hPa or ≥50 hPa or ≥10 hPa or ≥1 hPa or ≥0.1 hPa or ≥0.01 hPa or ≥0.001 hPa. The absolute pressure may be, for example, 0.001 hPa-900 hPa or 0.001 hPa-800 hPa or 0.001 hPa-700 hPa or 0.001 hPa-600 hPa or 0.001 hPa-500 hPa or 0.001 hPa-400 hPa or 0.001 hPa-300 hPa or 0.001 hPa-200 hPa or 0.001 hPa-100 hPa or 0.001 hPa-50 hPa or 0.001 hPa-10 hPa or 0.001 hPa-1 hPa or 0.001 hPa-0.1 hPa or 0.001 hPa-0.01 hPa. The absolute pressure may for example be 0.01 hPa-900 hPa or 0.01 hPa-800 hPa or 0.01 hPa-700 hPa or 0.01 hPa-600 hPa or 0.01 hPa-500 hPa or 0.01 hPa-400 hPa or 0.01 hPa-300 hPa or 0.01 hPa-200 hPa or 0.01 hPa-100 hPa or 0.01 hPa-50 hPa or 0.01 hPa-10 hPa or 0.01 hPa-1 hPa or 0.01 hPa-0.1 hPa. The absolute pressure may for example be 0.1 hPa-900 hPa or 0.1 hPa-800 hPa or 0.1 hPa-700 hPa or 0.1 hPa-600 hPa or 0.1 hPa-500 hPa or 0.1 hPa-400 hPa or 0.1 hPa-300 hPa or 0.1 hPa-200 hPa or 0.1 hPa-100 hPa or 0.1 hPa-50 hPa or 0.1 hPa-10 hPa or 0.1 hPa-1 hPa.The absolute pressure may be, for example, 1 hPa-900 hPa or 1 hPa-800 hPa or 1 hPa-700 hPa or 1 hPa-600 hPa or 1 hPa-500 hPa or 1 hPa-400 hPa or 1 hPa-300 hPa or 1 hPa-200 hPa or 1 hPa-100 hPa or 1 hPa-50 hPa or 1 hPa-10 hPa. The absolute pressure may be, for example, 10 hPa-900 hPa or 10 hPa-800 hPa or 10 hPa-700 hPa or 10 hPa-600 hPa or 10 hPa-500 hPa or 10 hPa-400 hPa or 10 hPa-300 hPa or 10 hPa-200 hPa or 10 hPa-100 hPa or 10 hPa-50 hPa. The absolute pressure may be, for example, 50 hPa-900 hPa or 50 hPa-800 hPa or 50 hPa-700 hPa or 50 hPa-600 hPa or 50 hPa-500 hPa or 50 hPa-400 hPa or 50 hPa-300 hPa or 50 hPa-200 hPa or 50 hPa-100 hPa. The absolute pressure may be, for example, 100 hPa-900 hPa or 100 hPa-800 hPa or 100 hPa-700 hPa or 100 hPa-600 hPa or 100 hPa-500 hPa or 100 hPa-400 hPa or 100 hPa300 hPa or 100 hPa-200 hPa. The absolute pressure may be, for example, 200 hPa-900 hPa or 200 hPa-800 hPa or 200 hPa-700 hPa or 200 hPa-600 hPa or 200 hPa-500 hPa or 200 hPa-400 hPa or 200 hPa-300 hPa. The absolute pressure may be, for example, 300 hPa-900 hPa or 300 hPa-800 hPa or 300 hPa-700 hPa or 300 hPa-600 hPa or 300 hPa-500 hPa or 300 hPa-400 hPa. The absolute pressure may be, for example, 400 hPa-900 hPa or 400 hPa-800 hPa or 400 hPa-700 hPa or 400 hPa-600 hPa or 400 hPa-500 hPa. The absolute pressure may be, for example, 500 hPa-900 hPa or 500 hPa-800 hPa or 500 hPa-700 hPa or 500 hPa-600 hPa. The absolute pressure may be, for example, 600 hPa-900 hPa or 600 hPa-800 hPa or 600 hPa-700 hPa. The absolute pressure may be, for example, 700 hPa-900 hPa or 700 hPa-800 hPa. The absolute pressure may be, for example, 800 hPa-900 hPa.Particularly preferred absolute pressure ranges are, for example, 0.001 hPa to 900 hPa, 0.001 hPa to 10 hPa, 0.001 hPa to 1 hPa or 0.01 hPa to 1 hPa.

[0056] In an embodiment, the hydrophilicity of the polymer surface measured according to the contact angle measurement can be higher than before the treatment, so that the contact angle is lower. Preferably, the hydrophilicity is increased by the treatment so that the contact angle is reduced by at least 5°. The contact angle measurement can be implemented according to DIN55660-2:2011-12. Compared with before the treatment, the contact angle can be reduced by more than 10%, preferably up to 17.5% or up to 25% or up to 30%. The contact angle can be reduced by 10%-15% or 10%-17.5% or 10%-20% or 10%-22.5% or 10%-25% or 10%-27.5% or 10%-30%. For example, the contact angle can be reduced from 75.4°±3.9° to 58.5°±5.4° by UV irradiation, which means a reduction of 22.5%. In another example, the contact angle is reduced from 90°-95° ​​to 65°-70°. The change in the contact angle depends on the treatment time.

[0057] In a particularly preferred embodiment, the fluorescent structure fluoresces in the blue portion of the visible spectrum. Preferably, the fluorescence is at a wavelength of 430nm-490nm. Structures that fluoresce at these wavelengths have been found to be particularly effective in reducing lens calcification in vivo.

[0058] Another aspect of the invention is the use of the products treated by the process of the invention in ophthalmic medical aids, in particular in intraocular lenses. These ophthalmic medical aids will benefit from the significant reduction of calcification in vivo by the polymers according to the invention.

[0059] Yet another aspect of the invention is an article comprising one or more polymers, optionally formed into an optical lens, an intraocular lens, or a "button" or preform of an optical lens or intraocular lens, wherein the one or more polymers comprise an acrylic structural mold and the one or more polymers comprise a fluorescent structure.

[0060] Preferably, the fluorescent structure is not extractable from the polymer preparation, is obtainable by intramolecular and / or intermolecular condensation of substituents and / or structural units of the polymer chain of the polymer, and / or comprises a lactone structure.

[0061] The article preferably has a refractive index between 1.50 and 1.59 in the dry state and / or between 1.45 and 1.47 in the deionized water hydrated state, measured at 589 nm and 20° C. "Dry state" refers to the state after drying in ambient air at 50° C. until no further weight loss occurs. "Deionized water hydrated" state refers to the state of the article after immersion in deionized water at 25° C. until no further weight gain occurs.

[0062] In an embodiment, in an article comprising a main body and a surface layer surrounding the main body, when the surface layer extends 300 μm toward the article, the fluorescent structure (i) exists in the main body, (ii) exists in the main body and in the surface layer, (iii) exists in the surface layer, or (iv) exists in the surface layer and not in the main body.

[0063] In one method example, the reduction of the residual monomer content is achieved by applying an absolute pressure of 0.001 hPa-900 hPa, the residual monomer content in the polymer is reduced to a concentration of 0.0001 wt.-% to <0.9 wt.-%, the irradiation and / or heating is carried out at an absolute pressure of 0.001 hPa-900 hPa, and the calcification tendency is reduced by a total of 50%-100%.

[0064] In another method example, the reduction of the residual monomer content is achieved by applying an absolute pressure of 0.001 hPa-10 hPa, the residual monomer content in the polymer is reduced to a concentration of 0.001 wt.-% to <0.7 wt.-%, the irradiation and / or heating is carried out at an absolute pressure of 0.001 hPa-200 hPa, and the calcification tendency is reduced by a total of 60%-95%.

[0065] In another method example, the reduction of the residual monomer content is achieved by applying an absolute pressure of 0.001 hPa-1 hPa, the residual monomer content in the polymer is reduced to a concentration of 0.001 wt.-% - <0.5 wt.-%, the irradiation and / or heating is carried out at an absolute pressure of 0.001 hPa-100 hPa, and the calcification tendency is reduced by a total of 70%-90%.

[0066] In another method example, the reduction of the residual monomer content is achieved by applying an absolute pressure of 0.01 hPa-1 hPa, the residual monomer content in the polymer is reduced to a concentration of 0.001 wt.-% to <0.5 wt.-%, the irradiation and / or heating is carried out at an absolute pressure of 0.01 hPa-10 hPa, and the calcification tendency is reduced by a total of 70%-90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 Photographs of the two explanted IOLs analyzed are shown.

[0068] Figure 2 show Figure 1 Micrographs of the surface and cross-section of a lens.

[0069] Figure 3 A lens "button" is shown, the left half of which has been untreated and the right half of which has been illuminated according to the invention to exhibit blue fluorescence.

[0070] Figure 4 Shown after 60 days incubation in solution L3 Figure 3 Two samples of the lens "button"

[0071] Figure 5 Photographs of lens "buttons" of different composition are shown which have been irradiated according to the invention on their right half (upper row) and after an incubation time of 60 days in solution L3 (lower row).

[0072] Figure 6 The lens "button" and the reference are shown during treatment at 200°C and 15hPa for 24 hours. Figure 3 Fluorescence image of the half-illuminated lens "button".

[0073] Figure 7 Two groups of lens "buttons" are shown after an incubation time of 226 days in solution L3, wherein the first group in the upper row is an untreated reference and the second group in the lower row has been treated according to the invention with 500 W / m on each side through quartz glass. 2 Intensity exposure for 72 hours.

[0074] Figure 8 Three groups of lens "buttons" are shown after an incubation time of 129 days in solution L3, wherein the first group in the upper row is an untreated reference, the second group in the middle row has been irradiated according to the invention, and the third group in the lower row has been heat-treated according to the invention.

[0075] Fig. 9 A cross section through the illuminated IOL and its blue fluorescence is shown.

[0076] Fig.10 A side view of the irradiated polymer without UV absorber and its blue fluorescence is shown. DETAILED DESCRIPTION

[0077] A group of two different types of explanted IOLs has been analyzed with regard to the effects of calcification. Figure 1 Photographs of these IOLs are shown.

[0078] From these IOLs, micrographs of the surface and cross-sections produced by microtome cutting have been made to visualize the calcification structure and location. Figure 2Micrographs showing its surface and cross-section. It can be clearly seen that the calcium deposits are not only located on the surface, but also to some extent below the surface (up to a depth of about 60-70 μm).

[0079] Figure 3 An example of a polymer treated by UV irradiation using the method of the invention is shown in FIG. The lens "button" whose left half has been covered with aluminum foil has been irradiated with 500 W / cm in the range of 300 nm to 800 nm. 2 Irradiated for 12 days. Figure 3 In the figure, the difference between the untreated left part and the treated right part is clearly visible. The treated half shows blue fluorescence with a maximum value between 430nm and 490nm.

[0080] To investigate the effectiveness of the anti-calcification treatment, two of these half-treated samples have been used in an in vitro calcification test, in which they were stored for 60 days in an incubator at 35°C in solution L3 as described above. Figure 4 Two samples after the incubation time are shown. While the untreated half is almost completely covered with calcium deposits, the treated half is almost free of any deposits.

[0081] Figure 5 Another group of four intraocular lens "buttons" shown in were subjected to the same test conditions. The four "buttons" differed in the added impurities. In this experiment, the influence of common impurities that may be present in polymers on the production of fluorescent structures was studied. Samples 1-3 contained 0.1 wt.-% MA, 1 wt.-% DGMA and 1.5 wt.-% EGDMA as examples of monomer treatment and crosslinker residues, while sample 4 was a pure reference. The photographs show the lens "buttons" after half-side irradiation according to the present invention in the upper row. Their right half therefore shows a cyan fluorescence. In the lower row, the same "buttons" are shown after an incubation time of 60 days in solution L3. In this comparison, the half-side treated according to the present invention has almost no deposits, while the untreated half-side shows deposits to varying degrees. The results show that impurities do not adversely affect the fluorescence production or the calcification-reducing effect.

[0082] A heat treatment variant of the method according to the invention has been shown in Figure 6 , which shows the lens "button" and Figure 3 Fluorescence image of a half-illuminated lens "button" (as a reference). After about 16 hours of treatment time, the same Figure 4 The UV irradiation test matches the fluorescence.

[0083] The long-term effect of this method has been investigated in a 226-day incubation trial in solution L3. Two groups of IOL "buttons" have been compared, namely an untreated reference group and one according to the invention in which the buttons were incubated at 500 W / m on each side through quartz glass. 2 The group with high intensity irradiation for 72 hours. Each group contains four identical samples. Figure 7 Two groups are shown after the incubation time, where the upper row is the untreated reference and the lower row is the group according to the invention. Even for this long-term test, the reduction in calcification is evident. While the reference sample groups showed a calcification tendency of (<30%, <30%, <25%, <30%), the irradiated sample groups had a calcification tendency of only (<5%, <10%, <5%, <10%). This clearly shows that the effect produced by the invention is a permanent effect.

[0084] A comparison has been carried out between UV treatment according to the invention and thermal treatment in a 129 day incubation test in solution L3. The main components of the polymers used are methyl methacrylate (MMA) and hydroxyethyl methacrylate (HEMA). Figure 8 The image stack image of the sample obtained according to the above measurement method is shown. The diameter of the sample image is about 10 mm. Three groups of lens "buttons" after incubation time are shown, where the first group in the upper row is the untreated reference, the second group in the middle row is the UV irradiation group, and the third group in the lower row is the heat treatment group. The irradiation has been with 290-310 nm and 1.2 mW / cm 2 UV light for five days or with 300nm and 7.14mW / cm 2 The heat treatment has been carried out for 17 hours at 200°C and 15hPa. Fluorescence excitation was carried out at 365±10nm. While the reference sample groups showed a calcification tendency of (<40%, <40%, <30%, <50%, <40%), the treated sample groups all had a calcification tendency of only <1%. The irradiated samples showed an almost complete suppression of calcification, while the heat-treated samples showed a high degree of calcification suppression.

[0085] To show the depth of effect that can be achieved, a comparison has been made between an IOL containing a UV absorber with a standard polymer and the same polymer without the UV absorber. Both samples have been illuminated with UV light to produce fluorescence. Fig. 9 A cross section through an irradiated IOL made from a standard polymer is shown. The thickness of the blue fluorescent layer is about 70 μm. Depending on the intensity and duration of the irradiation, the fluorescent layer thickness can be up to 200 μm. Fig.10A side view of an illuminated button made from the same polymer but without UV absorber and 3 mm thick is shown. It can be seen that the fluorescence generated by the UV illumination extends vertically through the entire button. The complete sample was photochemically illuminated. In order to visualize the fluorescence across the entire material thickness, a smaller excitation beam was used. Fluorescence is only seen in the middle excited area of ​​the button.

Claims

1. A method for reducing the calcification tendency of an article, optionally an article formed as an optical lens, an intraocular lens, or a button or preform of an optical lens or intraocular lens, the method comprising producing one or more fluorescent structures in or on the article, wherein the article comprises one or more polymers, One or more of the polymers comprises an acrylic structural motif.

2. The method of claim 1, wherein generating one or more fluorescent structures comprises partially or completely irradiating the article with UV radiation, preferably having a wavelength of 250 nm to 380 nm, and / or The article is heated above the glass transition temperature, Tg, of the polymer.

3. The method according to claim 1 or 2, wherein generating one or more fluorescent structures comprises generating the fluorescent structures in the polymer, in particular by intramolecular and / or intermolecular condensation of substituents and / or structural units of the polymer chain.

4. The method according to one or more of claims 1 to 3, wherein The calcification tendency of the polymer is reduced by at least 50% compared to before treatment, and / or The one or more fluorescent structures are produced such that the fluorescent intensity of the article is at least 80% of the maximum intensity achievable in the article by irradiation with UV radiation.

5. The method according to one or more of claims 2 to 4, wherein the heating is carried out at a pressure below the ambient pressure, preferably at an absolute pressure of ≤900 hPa.

6. The method according to one of the preceding claims, wherein before the step of producing the fluorescent structure, the residual monomer content in the polymer is low or reduced, preferably to a concentration of <1 wt.-% relative to the total amount of polymer.

7. The method according to any one of the preceding claims, wherein the method comprises The residual monomer content of the polymer is reduced, preferably by extraction or by applying a pressure below ambient pressure, preferably ≤ 900 hPa absolute.

8. The method according to any one of the preceding claims, wherein - the hydrophilicity of the polymer surface as determined according to contact angle measurement according to DIN 55660-2:2011-12 is higher than before the treatment, resulting in a lower contact angle, preferably at least 5° lower, and / or - The VLRH hardness measured according to DIN ISO 27588:2014-12 is higher than before treatment, preferably not more than 10% higher.

9. An article comprising one or more polymers, the article optionally being shaped into an optical lens, an intraocular lens, or a button or preform of an optical lens or intraocular lens, wherein one or more of the polymers comprises an acrylic structural motif, One or more polymers contain a fluorescent structure.

10. The article according to claim 9 or the method according to one of claims 1 to 8, wherein the fluorescent structure - cannot be extracted from polymer products, and / or - obtainable by intramolecular and / or intermolecular condensation of substituents and / or structural units of the polymer chain of the polymer, and / or - contains a lactone structure, and / or - fluoresces in the blue part of the visible spectrum, preferably at a wavelength of 430nm-490nm.

11. The product according to claim 9 or 10, wherein the product - has a refractive index of between 1.50 and 1.59 in the dry state and / or between 1.45 and 1.47 in the hydrated state with deionized water, measured at 589 nm and 20° C., and / or - wherein the fluorescence intensity of the article is at least 80% of the maximum intensity achievable in the article by UV irradiation, and / or -Has a calcification tendency of less than 10%.

12. The article according to one or more of claims 9 to 11, comprising a main body and a skin surrounding the main body, the skin extending 300 μm into the article, wherein the fluorescent structure (i) is present in the main body, (ii) present in the main body and in the surface layer, (iii) present in the surface layer, or (iv) is present in the surface layer and not in the main body.

13. The article according to one or more of claims 9 to 12 or the method according to claims 1 to 8, wherein - the polymer is a hydrophilic polymer and / or has a water absorption at a temperature of 25° C. of 5 wt.-% to 50 wt.-%, preferably of 20 wt.-% to 35 wt.-%, and / or - the polymer is a homopolymer or a copolymer of (meth)acrylate, acrylamide and / or alkylene glycol, and / or - The polymer is a homopolymer or a copolymer of monomers selected from the group consisting of methyl methacrylate (MMA), 2-hydroxyethyl methacrylate (HEMA), 2-hydroxyethyl acrylate (HEA), butyl acrylate (BA), lauryl acrylate (LA), ethoxyethyl methacrylate (EOEMA), methacrylic acid (MAA), acrylamide (AA), ethylene glycol dimethacrylate (EGDMA), diethylene glycol dimethacrylate (DEGMA), butanediol diacrylate (BDDA), N,N'-methylenebis(acrylamide) (MBA), ethylene glycol, propylene glycol, poly(ethylene glycol) phenyl ether acrylate (PEGPEA) and 2-phenylphenoxyethyl acrylate (OPPEA).

14. Article according to one or more of claims 10 to 19, obtainable by a process according to claims 1 to 9.

15. Use of the preparation according to claims 10 to 20 in ophthalmic medical aids, in particular in intraocular lenses.

Citation Information

Patent Citations

  • Intraocular lens and method of manufacturing the same

    US20170172728A1